Penerapan Metode Inkuiri Untuk Meningkatkan Kemampuan Komunikasi Matematik Siswa SMP di Kabupaten Cianjur - Endang Asad Fauzy; Yandu Hendipurwa; Wahyu Setiawan; Gagan Aditya Fauzan (Journal on Education, 2020)
This research was conducted at one private school in Cianjur Regency. The population in this study were all students in junior high schools in Cianjur. The sample in this study were eighth grade students of one of the junior high schools in Cianjur. from all the VIII classes, two classes were randomly selected to be the research sample. then from the two classes one class was chosen as the experimental class which was taught by the guided Inquiry method while the other class was used as a control class that received the usual learning treatment. The instruments used in this study took the form of a description of as many as five question numbers which included questions about students' mathematical communication skills. The method used in this study is a quasi-experimental method. In the study there are two groups, namely the control class and the experimental class. The experimental class was treated with the guided inquiry method and the control class gained conventional learning. To measure the ability of students' mathematical problems, the experimental class group and the control class are given a pretest before the learning treatment and posttest as difficult as the learning treatment. Based on the posttest data analysis shows that there are significant differences in mathematical communication skills where the mathematical creative thinking ability of students with the use of inquiry methods is better than conventional learning classes. This is because the steps of the inquiry method allow students to have enough time to assimilate and accommodate any relevant information so as to broaden and deepen students' understanding of the material being studied.